2001
DOI: 10.1161/hh1201.092035
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Pathways of Ca 2+ Sensitization in Porcine Coronary Artery

Abstract: Abstract-Alterations of the Ca 2ϩ sensitivity of contraction have been reported for porcine coronary artery, but the mechanisms are not clearly understood. We investigated the mechanism(s) of Ca 2ϩ sensitization in response to the thromboxane A 2 analogue (U46619). Our hypothesis is that different mechanisms of Ca 2ϩ sensitization could be distinguished by their distinct time courses. Therefore, we measured the time course of [Ca 2ϩ ] i and isometric force simultaneously in an intact artery after a single ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 21 publications
(21 reference statements)
4
31
0
Order By: Relevance
“…Fluoride is also a classical Ser/Thr phosphatase inhibitor (Shenolikar and Nairn, 1991) and is routinely included in extraction buffers to prevent dephosphorylation of proteins on Ser and Thr residues by endogenous phosphatases. On the other hand, previous studies examining the mechanisms of thromboxane A 2 mimetic U46619-induced arterial contraction have reported variable findings with regard to the contraction related to Rho-kinase activation (Nobe and Paul, 2001;Tasaki, et al, 2003;Wilson, et al, 2005). Therefore, it was consistent with the possibility that the hypoxia could decrease fluoride-or thromboxane A 2 mimetic-induced contraction inhibiting Rho-kinase activity.…”
Section: Discussionsupporting
confidence: 67%
“…Fluoride is also a classical Ser/Thr phosphatase inhibitor (Shenolikar and Nairn, 1991) and is routinely included in extraction buffers to prevent dephosphorylation of proteins on Ser and Thr residues by endogenous phosphatases. On the other hand, previous studies examining the mechanisms of thromboxane A 2 mimetic U46619-induced arterial contraction have reported variable findings with regard to the contraction related to Rho-kinase activation (Nobe and Paul, 2001;Tasaki, et al, 2003;Wilson, et al, 2005). Therefore, it was consistent with the possibility that the hypoxia could decrease fluoride-or thromboxane A 2 mimetic-induced contraction inhibiting Rho-kinase activity.…”
Section: Discussionsupporting
confidence: 67%
“…A similar bimodal appearance has been described for the thromboxane A 2 analogue U46619-induced contraction in porcine coronary artery (Nobe and Paul, 2001). The transient phase of contraction to U46619 was associated with Ca 2+ release from the sarcoplasmic reticulum and a protein kinase C (PKC)-mediated Ca 2+ release, while in the sustained phase, involves Ca 2+ influx from the extracellular space and Rho-kinase-mediated Ca 2+ sensitization (Nobe and Paul, 2001). The present study has revealed that the ERK1/2 inhibitor SB386023 (10 5 M) and the calcium influx inhibitor, nifedipine, significantly decreased the sustained contraction.…”
Section: Discussionsupporting
confidence: 53%
“…The increase of intracellular calcium induced via endothelin ET B receptor activation consists of two phases: one rapid and one sustained. The rapid phase of calcium release induced by agonist via endothelin ET B receptors, is supposed to occur via the inositol 1, 4, 5-triphosphate [Ins(1, 4, 5)P3]-mediated calcium release from the sarcoplasmic reticulum (Nobe and Paul, 2001). This was, however, not inhibited by nifedipine or SB386023.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with findings in tracheal smooth muscle (13) and in rat aorta and small mesenteric arteries (9) where Rho kinase regulates the Ca 2ϩ entry upon activation of muscarinic and ␣ 1 -adrenergic receptors, respectively. However, this involvement is probably dependent on the type of receptor and/or vascular bed since inhibition of Rho kinase did not significantly alter the Ca 2ϩ influx evoked by thromboxane A 2 in either porcine coronary artery (17) or pulmonary arteries (7).…”
Section: Discussionmentioning
confidence: 93%